2009
DOI: 10.1007/s10660-009-9027-3
|View full text |Cite
|
Sign up to set email alerts
|

Beyond e-business models: the road to virtual worlds

Abstract: Virtual Worlds (or, VWs) are an intriguing field of research. In particular, VWs appear to create new opportunities for integrating the business of the firm with Information Technology (or, IT). This article is a first attempt to address the topic of how owning andmaintaining a VWcan impact on the businessmodels of firms and on the literature on business models, and VWs are examined in order to understand the relationship between them. A qualitative methodology is proposed to sketch a radar map framework, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…A smaller share of articles (7 %) is related to business models in the context of social commerce (Cagnina and Poian 2009;Cheema 2008;Dhar and Ghose 2010;Greiner and Wang 2010;Lehdonvirta 2009;Oestreicher-Singer and Zalmanson 2009;Pelaez et al 2013;Scarle et al 2012). They address different social media platform types such as social shopping websites (3 articles), social gaming websites and virtual worlds (2 articles), as well as group buying websites (1 article), presentation sites (1 article) and social networking sites (1 article).…”
Section: Research Theme: Business Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A smaller share of articles (7 %) is related to business models in the context of social commerce (Cagnina and Poian 2009;Cheema 2008;Dhar and Ghose 2010;Greiner and Wang 2010;Lehdonvirta 2009;Oestreicher-Singer and Zalmanson 2009;Pelaez et al 2013;Scarle et al 2012). They address different social media platform types such as social shopping websites (3 articles), social gaming websites and virtual worlds (2 articles), as well as group buying websites (1 article), presentation sites (1 article) and social networking sites (1 article).…”
Section: Research Theme: Business Modelsmentioning
confidence: 99%
“…Lehdonvirta (2009) examines the drivers of the revenue model of selling virtual goods for real money, which is an increasingly common revenue model for social networking sites and other online services as well. In addition, Cagnina and Poian (2009) propose a framework to identify value drivers in virtual worlds in order to support firms looking to implement virtual worlds as a successful business model. In sum, researchers who have studied social commerce related business models have focused on only few types of social commerce platforms such as virtual worlds (e.g.…”
Section: Research Theme: Business Modelsmentioning
confidence: 99%
“…Immersion refers to becoming part of the experience and positively impacts on brand attitude and product knowledge [6]. Csíkszentmihályi [12,13] and Nah et al [53] also indicated that flow experience allows people focus on their actions and produce the sense of immersion.…”
Section: Perceived Riskmentioning
confidence: 99%
“…This study aimed to apply Daugherty et al [15] and Pine and Gilmore [66] research to explore the effects of sequential combinations of consumer experiences on product knowledge [6,15,43,78], brand attitude [6,15,43,78], and perceived risk [18,25,27,47,79,80]. Four kinds of sequential combinations of consumer experiences were designed: exposing to VE escapist preceding DE (VE escapist → DE), exposing to VE education preceding DE (VE education → DE), exposing to VE escapist preceding IDE (VE escapist → IDE), and exposing to VE education preceding IDE (VE education → IDE).…”
Section: Introductionmentioning
confidence: 99%
“…We focus on exploring the stakeholders' views and attitudes towards the v-HRM initiatives, and what value components are perceived by different types of stakeholders. In addition, past literature has shown that the potential value of virtual worlds can be influenced by different facilitators [35], and thus we aim to identify v-HRM facilitators that can drive the values that are realized by stakeholders. …”
Section: The Impact Framework-a Conceptual Modelmentioning
confidence: 99%